Conventions for unconventional language: Revisiting a framework for spoken language features in autism. (June 2022) - Luyster, Rhiannon J; Zane, Emily; Wisman Weil, Lisa
Background and aims: Autism has long been characterized by a range of spoken language features, including, for instance: the tendency to repeat words and phrases, the use of invented words, and "pedantic" language. These observations have been the source of considerable disagreement in both the theoretical and applied realms. Despite persistent professional interest in these language features, there has been little consensus around terminology, definitions and developmental/clinical interpretation. Main contribution: This review paper updates and expands an existing framework for unconventional language in autism to include a broader range of non-generative (echolalia and self-repetition) and generative (idiosyncratic phrases, neologisms and pedantic language) features often observed in the language of individuals on the autism spectrum. For each aspect of the framework, we review the various definitions and measurement approaches, and we provide a summary of individual and contextual correlates. We also propose some transitional language features that may bridge non-generative and generative domains (e.g., mitigated echolalia and gestalt language). Conclusions: This updated framework offers a unified taxonomy and nomenclature that can facilitate further investigation and interpretation of unconventional language in autism. Implications: There are important implications of this work for our understanding of the complex interplay between autism and language development. Equally important are the clinical ramifications that will guide evidence-based practice in assessment and intervention for individuals on the autism spectrum.